Gamma-ray burst afterglows as probes of environment and blast wave physics. I. Absorption by host-galaxy gas and dust - Starling, R.; Wijers, R.; Wiersema, K.; Rol, E.; Curran, Peter; Kouveliotou, C.; van der Horst, A.; Heemskerk, M. (Institute of Physics Publishing, 2007)
We use a new approach to obtain limits on the absorbing columns toward an initial sample of 10 long gamma-ray bursts observed with BeppoSAX and selected on the basis of their good optical and near-infrared (NIR) coverage, from simultaneous fits to NIR, optical, and X-ray afterglow data, in count space and including the effects of metallicity. In no cases is a Milky Way-like ( MW) extinction preferred when testing MW, LMC, and SMC extinction laws. The 2175 angstrom bump would in principle be detectable in all these afterglows, but is not present in the data. An SMC-like gas-to-dust ratio or lower value can be ruled out for four of the hosts analyzed here ( assuming SMC metallicity and extinction law), while the remainder of the sample have too large an error to discriminate. We provide a more accurate estimate of the line-of-sight extinction and improve on the uncertainties for the majority of the extinction measurements made in previous studies of this sample. We discuss this method for determining extinction values in comparison with the most commonly employed existing methods.